2017
DOI: 10.1016/j.riem.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar psicológico en estudiantes de carreras de la salud

Abstract: A theoretical model of psychological well-being that encompasses 6 distinct dimensions of wellness (Autonomy, Environmental Mastery, Personal Growth, Positive Relations With Others, Purpose in Life, Self-Acceptance) was tested with data from a nationally representative sample of adults (iV -1,108), aged 25 and older, who participated in telephone interviews. Confirmatory factor analyses provided support for the proposed 6-factor model, with a single second-order super factor. The model was superior in fit over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
(35 reference statements)
1
3
0
23
Order By: Relevance
“…Under this line, the results showed that most of the population studied has medium to low levels of PW, after considering the global scores. In the analysis of the sociodemographic variables, men had the lowest levels, while those living in consensual union and those who came from outside the host city had the lowest levels, similar to what was found in a study carried out in Chile, in students of health careers (19). It should be noted that the scale was validated with the study population and that better adjustments were found with only 4 dimensions and not with 6, as in the original Ryff scale, similar to the validation made in Mexican university students in 2017 (31).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Under this line, the results showed that most of the population studied has medium to low levels of PW, after considering the global scores. In the analysis of the sociodemographic variables, men had the lowest levels, while those living in consensual union and those who came from outside the host city had the lowest levels, similar to what was found in a study carried out in Chile, in students of health careers (19). It should be noted that the scale was validated with the study population and that better adjustments were found with only 4 dimensions and not with 6, as in the original Ryff scale, similar to the validation made in Mexican university students in 2017 (31).…”
Section: Discussionsupporting
confidence: 83%
“…In general, people with high levels of PW have been shown to cope better with the demands and challenges of the environment (18), are more productive and valued at work, endure pain better, take better care of their health, show more flexible thinking and accept different opinions (14); in addition, some research shows that PW has a role in both prevention and recovery from physical illness (7). Other studies have shown that an education based on psychological wellbeing improves students' learning and creativity (19), and helps them to be more motivated and perform better academically (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…El término bienestar psicológico es caracterizado por ser multidimensional y, como sostienen Barrientos et al (2017), puede ser definido como el crecimiento personal y las capacidades de un individuo, a partir de las cuales éste muestra indicadores de un funcionamiento positivo. Constituye, afirman los mismos, una experiencia personal que se construye a lo largo del tiempo con el desarrollo psicológico del sujeto y con la capacidad de relacionarse positivamente con sus experiencias, teniendo en cuenta la incorporación activa de medidas positivas y no solamente la ausencia de aspectos negativos vivenciados.…”
Section: Optimismo Y Bienestar Psicológicounclassified
“…Diferentes estudios han demostrado como el contexto sociocultural influye en el nivel bienestar y en el significado social e individual de "estar bien", "sentirse bien" o "tener bienestar" (Ryff, 1989;Schimmack, Radhakrishnan, Oishi, Dzokoto, & Ahadi, 2002;Triandis, 1994;D´Anello, 2006, Muratori & Bobowik, 2015. En este sentido, se ha visto, como el contexto disciplinar y académico puede estar relacionado con el nivel de bienestar psicológico de los estudiantes de diferentes carreras (Veliz-Burgos & Apodaca, 2012), y como el nivel BP general varía en función del año académico que esté cursando el estudiante, no demostrándose si, una línea clara de variación (Sandoval, Dorner & Véliz, 2017).…”
Section: Can Optimism Mediate the Negative Effect Of Trait Anxiety Onunclassified